Optimization of Arabica Coffee (Coffea arabica L.) Shoot Cutting Growth Using Plastic Bottle Covers and Goat Urine Treatments - Safinah Safinah; Sri Darmanti; Yulita Nurchayati (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
Arabica coffee (Coffea arabica L.) is a high-value commodity, yet its productivity in Indonesia remains low due to suboptimal cultivation techniques. One of the main constraints is the limited availability of quality seedlings, which is influenced by propagation methods. Vegetative propagation through shoot cuttings is widely used, but often constrained by low survival and root formation rates. The application of plastic bottle covers and goat urine has the potential to improve propagation success by creating a favorable microclimate and supplying growth regulators and essential nutrients. This study examined the effects of plastic bottle cover types and goat urine concentrations on the growth of C. arabica shoot cuttings. The experiment was arranged in a 3×3 factorial Completely Randomized Design (CRD), with two factors: plastic bottle cover types (no cover, open-cap cover, and closed cover) and goat urine concentrations (0, 100, and 180 mL/L). Observed parameters included shoot length, shoot number, leaf length, leaf number, root length, root number, and root diameter. Data were analyzed using analysis of variance (ANOVA) followed by Tukey’s Honestly Significant Difference (HSD) test at a 5% significance level. The results showed a significant interaction between cover type and goat urine concentration. Combining a closed cover with 100 mL/L goat urine produced the highest shoot growth, cutting survival rate, and rooting percentage, while optimal root development was obtained with the closed cover and 180 mL/L goat urine. The most effective treatment was the closed cover combined with 100 mL/L goat urine.